Strategies and Optimizing the Role of Productive Waqf in Economic Empowerment of the Ummah - Ardiyansyah, Rian; Kasdi, Abdurrohman (UIN Sunan Kudus, 2021)
The understanding and empowerment of waqf assets among Muslims has undergone significant changes in both paradigm and operational practices. The development of productive waqf aims to achieve social justice and improve the welfare of people. Therefore, productive waqf has two visions at once, destroying unequal social structures and providing fertile land for the welfare of the people. This research method uses a qualitative method with a descriptive-analytical approach. The data used were secondary data, namely, literature studies or relevant previous research results. The results of his research show that waqf plays an important role as an instrument to empower the economy of the people. Waqf has played an important role in the social, economic, and cultural development of society. There are at least four basic problems with the Islamic da'wah movement. First, the problem of poverty, both in terms of the economy and limited facilities and physical needs, creates a culture of poverty. Second, the twisting of the kemikinan prompts the symptoms of underdevelopment. Third, there was an exclusive and involutive attitude. Finally, the weakness of the institutions for accommodating participation and the weakness of the cooperation mechanism to wage a systematic struggle. Thus, waqf is an alternative that is expected to provide solutions to these problems. Therefore, the optimal management of waqf objects is required.